Career concern as predictor of turnover intention: Empirical evidence from education industry - Nawaz, Muhammad Shahid; Pangil, Faizuniah (2016)
Retaining the best employees is of high concern for most organizations and this issue has become a significant focus of attention for many researchers. For this reason, there is the necessity to investigate the factors which influence the employee turnover intention behavior in the organization, specifically to examine the effect of Career concern on turnover intention. Career concern was conceptualized by Adult Career Concern Inventory (ACCI) which used to measure and operationalized the Career concern variable. Data was collected to investigate the relationships in a sample of 270 full time faculty members employed in different private universities of Pakistan. The Finding of this paper indicated that career concern has been found as one of the most important predictor of employee turnover intention. This implies that, if employees are highly concerned about their career (i.e. the progression of their career) they are more likely to leave their current organization, especially if their prospect of advancing their career is not clear or non-existence.